Bufalin inhibits human diffuse large B-cell lymphoma tumorigenesis by inducing cell death through the Ca2+/NFATC1/cMYC pathway. (30th October 2020) - Song, Jincheng; Zou, Dan; Zhao, Xiaoxuan; Chen, Yang; Lv, Fei; Wang, Song; Sui, Dan; Han, Qiuyue; Yang, Chunjiao; Wang, Ximing; Liu, Bofang; Deng, Mingming; et al.
Abstract: The 5-year survival rate of diffuse large B-cell lymphoma (DLBCL) can reach 60%. However, nearly half of patients undergo relapse/refractory issues with a survival period of less than 2 years. New therapeutic approaches are therefore needed to improve chemotherapy efficacy and patient survival. Bufalin (BF), isolated from the traditional Chinese medicine Chansu, has been reported to play an anticancer role in multiple cancer cell types. However, there are few reports of the effects of BF on the growth of DLBCL. In the present study, we demonstrated that BF exerts antitumor activity in DLBCL cells, both in vitro and in vivo . Treatment of DLBCL cells with BF resulted in increased proliferation and apoptosis in a dose- and time-dependent manner. Daily intraperitoneal injection of 1.5 mg/kg BF significantly delayed DLBCL xenograft growth in NOD/SCID mice without affecting body weight. Bioinformatics analysis showed that BF may regulate NFATC1 protein and affect expression of its downstream gene, cMYC. Our results suggest that BF can attenuate NFATC1 translocation by reducing the intracellular calcium concentration; BF may also have a low synergistic effect with cyclosporin A. In conclusion, we demonstrated that BF exerts antitumor activity that is mediated at least in part by the Ca 2+ /NFATC1/cMYC pathway. Our findings suggest that BF can be effectively applied as a novel potential therapeutic agent for DLBCL.